2018
DOI: 10.1186/s40538-018-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effect of aqueous and ethanolic extracts of neem leaves, stem bark and seeds on fungal rot diseases of yam and cocoyam

Abstract: Background: Fungal rot diseases of white yam (Discorea rotundata) tubers and cocoyam (Colocasia esculenta) are the major post-harvest challenges in the availability of these root tubers. The use of biological extract of plants will prevent post-harvest losses without any negative health challenge. Methods: Microwave-assisted method of extraction was used for both aqueous and ethanolic extracts of neem samples. Fungal-rotted yam and fungal-rotted cocoyam samples were collected, and fungi from them were cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In their study, soil amendment with Neem was also observed to be effective in enhancing the plant size and seed germination with minimum seedling mortality by F. oxysporum. Ezeonu et al (2018) also gave similar report regarding the effectiveness of Neem seed, bark, and leaf ethanolic extracts against fungal pathogens namely, Aspergillus oryzae, A. niger, Rhizopus stolonifer, A. ochraceus, and Lasiodiplodia theobromae responsible for rot diseases in cocoyam and yam plants. Obtained results agree with the findings of Ali et al (2017b) who discovered that nano emulsions of Neem represent excellent antifungal activity against many phytopathogenic fungi such as follows: S. rolfsii and Rhizoctonia solani that cause collar rot, dampingoff, wilting, and dry root rot under field conditions.…”
Section: Pot Trialmentioning
confidence: 61%
“…In their study, soil amendment with Neem was also observed to be effective in enhancing the plant size and seed germination with minimum seedling mortality by F. oxysporum. Ezeonu et al (2018) also gave similar report regarding the effectiveness of Neem seed, bark, and leaf ethanolic extracts against fungal pathogens namely, Aspergillus oryzae, A. niger, Rhizopus stolonifer, A. ochraceus, and Lasiodiplodia theobromae responsible for rot diseases in cocoyam and yam plants. Obtained results agree with the findings of Ali et al (2017b) who discovered that nano emulsions of Neem represent excellent antifungal activity against many phytopathogenic fungi such as follows: S. rolfsii and Rhizoctonia solani that cause collar rot, dampingoff, wilting, and dry root rot under field conditions.…”
Section: Pot Trialmentioning
confidence: 61%
“…The genera Acacia sp., Brassica sp. and the species Melia azedarach L., Rosmarinus officinalis L. and Zingiber officinale R. were identified in 2.48% 11.94 FEREIRA et al, 2014;ZAKA et al, 2019;FREIRE;SANToS, 2018;HASSAN et al, 2013;KUMAR et al, 2012;PARMAR, 2013;KUMAR et al, 2011;NAHAR;SHAMSI, 2020;NNEDINMA et al, 2019;ARSHAD et al, 2019;AL-SAMARRAI et al, 2012;JALEEL et al, 2020;AHMED et al, 2019;MEENA et al, 2020;FIAZ et al, 2012;PoDERoSo et al, 2016;ATRI;TIWANA, 2019;MAHMUD;HoSSAIN, 2017;REHMAN et al, 2019;TANVEER et al, 2016;GARCIA et al, 2019;HUSSAIN et al, 2015;EZEoNU et al, 2018;DA SILVA et al, 2014 BETTIoL., 2020;SHAPIRo-ILAN et al, 2013;KHAN et al, 2020;MUNoZ;QUILoDRAN;NAVIA, 2014 CHAND et al, 2016;TANVEER et al, 2016;SALJoQI et al, 2012;SIDDIQUE et al, 2019;ALSAHLI et al, 2018;HAN et al, 2018;FU et al, 2018.…”
Section: Developmentmentioning
confidence: 99%
“…A broad diversity of fungi genera are attack on vegetables and fruits, which creates quality issues connected to many aspects such as limited shelf life, organoleptic characteristics, dietary values and a results a huge economic loss (Diaz et al, 2011). The application of plants extracts for the diseases management of crops and plants poses little environmental risk and economically viable;, the herbs are accessible to the growers in the tropics, developing countries and numerous areas of the globe that have no easy reach to the synthetics pesticides (Chukwuma et al, 2018). The extracts of plants derived from stem, rhizome, fruits, flowers, roots, leaves and bark consist of numerous bioactive substances that have antifungal and antimicrobial properties (Kanal, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These functional groups reported antibacterial and antifungal potential (Basir and Javid, 2013;Javid et al, 2015). Although several studies have evaluated the phytochemicals, FTIR and antimicrobial activities of neem extracts against a broad range of pathogens (Ali et al, 2022;Amadioha, 1999;Chukwuma et al, 2018;Govindachari et al, 1998;Khanal, 2021;Khajista, 2013;Lethika et al, 2013;Nwali et al, 2018;Oyekanmi et al, 2021), but the antifungal activity against the plant pathogenic fungi and FTIR measurements together of neem extracts remains elusive. The current study was aim to find a plant product, which can be used as a substitute of commercially available chemical fungicide.…”
Section: Introductionmentioning
confidence: 99%